Pengembangan Sistem Pengelolaan Permintaan Olah Data Dengan Notifikasi Otomatis Di Badan Pusat Statistik Provinsi Kepulauan Bangka Belitung - Ardi Ramadani; Yang Agita Rindri; Indra Irawan (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
This research aims to develop a web-based data request management system with automatic notifications at the BPS Bangka Belitung Province to overcome manual system constraints that cause response delays and difficulties in status monitoring. The method used is Rapid Application Development (RAD), comprising four stages: requirements planning, system design using UML, implementation using Laravel 11 and MySQL, and deployment. The system involves four actors: Admin, PST Officer, Data Processor, and Customer, with an integrated workflow from submission to output delivery, accompanied by automatic email notifications. User Acceptance Testing results from 13 respondents indicated an excellent acceptance rate of 90.6%, demonstrating that the system can improve service efficiency and the transparency of data request processes. The system successfully addresses documentation challenges, facilitates internal coordination between officers, and enables customers to track request status independently.